Productivity Improvement for Unit Terminal Container using Lean Supply Chain Management and Single Minute Exchange of Dies (SMED): A Case Study at Semarang Port in Indonesia - Kusrini, Elisa; Parmasari, Anggita Noviyanti (International Journal of Integrated Engineering, 2020)
The main business process in Unit Terminal Container (UTC) is collecting containers from the hinterland or other ports for transportation to the destination. The company that operates UTC is required to improve services in supporting the smooth process of goods services and creating optimal port productivity. This study aims to increase UTC productivity using the concept of lean supply chain management by analyzing using value stream mapping (VSM) and improvement with Single Minute Exchange of Dies (SMED) and 5S (Seiri, Seiton,Seiso, Seiketsu, Shitsuke). Base on result of VSM, it is obtained the highest waste in unnecessary motion (18.574%) and transport of documents (18.154%) with value added activities of 60.81% and the percentage of non value added activities of 39.19%. Improvements using SMED method and 5S resulted in increased efficiency from 60.81% to 70.20%.